Influencing Firm Value: Profitability, Capital Structure, and Ownership in Indonesian Mining Companies - Annisa Zalfa Nur Alya Hardiansyah; Andy Setiawan (Accounting Student Research Journal, 2023)
This study examines the impact of profitability, capital structure, and managerial ownership on firm value, with firm size as a control variable. The study population consists of mining companies listed on the Indonesia Stock Exchange between 2018 and 2021, with 100 samples obtained through purposive sampling. The analysis technique employed panel regression analysis. The results indicate that profitability and capital structure have a significant positive effect on firm value, while managerial ownership has a negative significant effect on firm value. These findings have implications for mining companies in Indonesia to focus on improving profitability to enhance firm value.